Aprepitant: a neurokinin-1 receptor antagonist for the treatment of chemotherapy-induced nausea and vomiting. Issue 5 (1st October 2004) - Navari, Rudolph M
Chemotherapy-induced nausea and vomiting (CINV) is associated with a significant deterioration in quality of life, and although the use of 5-hydroxytryptamine-3 (5-HT3 ) receptor antagonists plus dexamethasone has significantly improved the control of acute CINV, delayed nausea and vomiting remain a significant clinical problem. Aprepitant (Emend ®®, Merck) is the first agent available in the new drug class of neurokinin-1 receptor antagonists. When added to a standard regimen of a 5-HT3 receptor antagonist and dexamethasone in patients receiving highly emetogenic chemotherapy, it improves the complete response rate of acute CINV. Aprepitant also improves the complete response of delayed CINV when used in combination with dexamethasone compared with dexamethasone alone. Based on these studies, new guidelines for the prevention of CINV have been developed for patients receiving highly emetogenic chemotherapy. The use of aprepitant in patients receiving moderately emetogenic chemotherapy will await the review and analysis of recently completed Phase III trials. Aprepitant is a substrate, a moderate inhibitor and an inducer of cytochrome P450 (CYP)3A4 and CYP2C9. Drug interactions should be monitored when aprepitant is coadministered with agents affected by CYP3A4 and CYP2C9 isoenzymes. The safety and efficacy of aprepitant has not been established in pediatric or adolescent patients, and aprepitant has not been evaluated in the treatment of patients with established nausea and vomiting. Future studies may consider the use of aprepitant with current and other new agents in moderately and highly emetogenic chemotherapy, as well in the clinical settings of multiple-day chemotherapy and bone marrow transplantation.